Primary amenorrhoea: a diagnostic dilemma - Narasegowda, Deepika; Kumar, Arun; Aparna, K. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary amenorrhoea is defined as absence of menses in females by the age of 14 years in the absence of secondary sex characters or absence of menses by the age of 16 years regardless of appearance of secondary sex characters. Incidence of Extrapulmonary TB (EPTB) is increasing in young women throughout the world. We report a case of 24 year unmarried female with primary amenorrhoea secondary to genital tuberculosis apparently having no sings & symptoms of tuberculosis.